THE POSSIBILITY OF UTILIZATION OF THE EQUATORIAL ATMOSPHERE RADAR (EAR) ON STUDY THE EFFECT OF GRAVITY WAVES ON A CORRUGATED STRUCTURE OF REFLECTION SURFACE - Eddy Hermawan (Lembaga Penerbangan dan Antariksa Nasional, 2005)
We have introduced a new Aquatorial Atmosphere Radar (EAR), a collaboration project between Research Institude for Sustainable Humanosphere (RISH), Kyoto University, Japan and the Indonesian Natioanal Institute of Aeronautics and Space (LAPAN) at Kototabang, Bukittinggi, West Sumatera. This radar is mainly concerned to observe winds and turbulence in the troposphere and lower stratosphere with a good time the EAR are still developing. In this paper, one possibility an application of EAR on study effects of gravity waves on a corrugated surface is discussed. For the referance, we investigated the azimuth angle variations of clear air echoes in the troposphere and lower stratosphere by using the MU (Middle and Upper Atmosphere) radar in Shigaraki, Japan (34˚51’N; 136˚06’E). We used a data set collected on November 4-5, 1986 by steering the antenna beam into 12 oblique positions at the same zineth angle of 6˚ and the azimuth angle being changed every 30˚. We have detected considerable amplitudes in the azimuth angle variations of echo power, which was continuous along altitude. We also found time evolution of the azimuth angle variations of echo power. The observed azimuth angle variations of echo power suggest that the reflection surface is affected by propagating gravity wave. As a preminary result, we present characteristics of zonal and meridional wind velocity observed with EAR on May 24-25, 2001 over Kototabang after observations of the variations of meridional wind velocity from September to December 2001 as one of the most important parameter needed to explain the mechanism of gravity waves is also discussed.